Pressure-induced phase transitions in weak interlayer coupling CdPS₃ - Niu, Mengmeng (2022)
Metal phosphorus trichalcogenides (MPX3: M = Fe, Co, Ni, Cd, Mn; X = S or Se) represent a family of two-dimensional (2D) layered materials with an exceptional response to high pressure and a remarkable structural flexibility originating from the weak interlayer coupling. Despite their interest for applications, the knowledge about pressure-driven phase transitions of cadmium compounds is still limited. In this paper, we fill this gap and provide an accurate description of the structural evolution of CdPS3 by combining high-pressure experiments and first-principle calculations. We have performed high-throughput screening of the low-energy stacking configurations and found a phase evolution starting with C 2 / m space group at 12 GPa using the generalized evolutionary metadynamics method. Then, high-pressure experiments have been used to reveal a structural transition from phase-I (C 2 / m) to phase-II (R 3 ¯) to phase-III (R 3 ¯), which is marked by the appearance and vanishing of the Raman band at approximately 30-250 cm-1 in good agreement with our theoretical predictions. Our study paves the way to the understanding of pressure-induced phase transitions in weak interlayer coupling 2D CdPS3 materials.